The decline of traditional social institutions in a Malay peasant community - Wan Hashim Wan Teh (Universiti Kebangsaan Malaysia, 1977)
This article discusses some basic social and socio-economic institutions in a Malay peasant community. The institutions are: Kerah, Hantar, Serah, Berderau, Meminjam, Gotong-Royong and various types of Kenduri; i.e., institutions that compel individuals to come together as a group and as members of a community. The discussion on the characteristics of these institutions tells us the nature of a small village community which is closely-knit where group solidarity, mutual help and cooperation are the norm and ideology of the community. The writer agrees that through the process of modernization and commercialization, these institutions are undergoing modifications and in fact declining in their importance. This, to a certain extent, reflects the present nature of the community studied. Through the impact of forces of change, membership of the community is being transformed from a community-oriented to an individual-oriented one. The writer believes that this process of change is similarly occurring in other parts of the peasant community in Peninsula Malaysia, even though the degree of change may not be the same.